The Changing secondary school curriculum : readings - Alexander, William M. (New York : Holt, Rinehart and Winston, Inc., 1967)
This Book is intended to be a major guide and resource for all who study the American secondary school curriculum. It is more than a textbook in the traditional sense of a book of facts and principles based upon the writer's point of view alone; it is a collection of opinions and theories that reflect various positions on complex and controversial curriculum issues. The reader is left free to make his own judgments and conclusions on these issues using the readings as a guide. The facts of a changing curriculum are clear. Schools that try to educate all of the children of all of the people cannot merely add courses and activities when the pupil population continues to explode. American education is not without its quest for excellence. The failures in our secondary curriculum became most apparent after Russia orbited the first Sputnik in 1957; the resultant international academic tensions rivaled perhaps the most significant political and social issues. Furthermore, the American secondary school curriculum has changed more this past decade than in at least the three to four preceding ones combined.
Part I. The Bases of secondary school curriculum improvement -- Part II. Toward a changing curriculum -- Part III. Issues in secondary school curriculum improvement -- Part IV. The Secondary school curriculum of the future.
Includes index.
Keywords: EDUCATION